Excerpt from the 'Īsāwiyya recited liturgy (ḥizb) (16:02-19:13). - Īsāwiyya of La Marsa. (Tufts University. Tisch Library., 2020)
Further tempo increase and rise in pitch of the Īsāwiyya of La Marsa recitation at their devotional ceremony (ḥaḍra) during their pilgrimage to the shrine of Sīdī 'Alī Ḥaṭṭāb.; Keywords: Sufi recitation; ritual music; 'Īsāwiyya Sufi order; Tunisia.; Accompanies chapter 2, musical example 2.3 of: Jankowsky, Richard C. Ambient Sufism: Ritual Niches and the Social Work of Musical Form. Chicago: University of Chicago Press, 2020.